Pengembangan Model Prediksi Kebutuhan Air Bersih terhadap Keseimbangan antara Pemasok Air Bersih dengan Kebutuhan Air Bersih Menggunakan Sistem Dinamis pada PT. X Pengolahan Hasil Laut Di Jawa Timur - Yayok Suryo Purnomo; Dea Febrica Ervina (Prosiding ESEC, 2023)
In running the production process of this company requires a large volume of clean water. Meanwhile, the company's supply of clean water is only supplied by PDAM, second party supplies, and the results of the water treatment plant. This study aims to analyze the prediction of water demand for the balance between clean water suppliers and clean water demand based on increased production. This approach is carried out with a dynamic system model and with the help of stella 9.0.2 software. The methods used in this study are problem identification, making dynamic hypotheses, model validation, and model evaluation. from the simulation results show that the amount of production in years 2 to 10 has increased, namely in year 2 as much as 1396.41 tons and in year 10 it reached 1546.64 tons. in years 4 and 6 the water supply has decreased which is not proportional to the required water consumption. However, in year 6 to year 10, the volume of clean water supply continues to increase and has fulfilled the total volume of water demand. Therefore, a policy is needed to increase the supply of clean water from the PDAM or supply water from within the company itself, namely by expanding the land for water treatment plants or utilizing surface water sources, namely well water.